Sequence-admittance-based stability analysis for multiple parallel converters - Chongxi Jiang; Yanxue Yu; Pengfei Hu; Yuchao Shi; Jing Wu; Guofeng Xu (Energy Reports, 2023)
With the development of energy storage system, the voltage-controlled converters (VCCs) that can achieve voltage and frequency support have become hot spots in both theory and practice. Therefore, apart from the traditional multiple parallel current-controlled converters (CCCs), multiple parallel VCCs and multiple parallel hybrid-controlled converters (HCCs) consisting of both the CCCs and VCCs have emerged, which makes stability issues of multi-converter grid-connected systems more complex. To cope with stability concerns related to different kinds of multiple parallel converter systems, this paper analyzes the interactive process of circuit-coupling and frequency-coupling among grid-connected converters and develops equivalent sequence-admittance-based stability analysis models. Based on the proposed models, stability recognition of grid-connected CCCs, VCCs and HCCs are derived. Finally, the effectiveness of the built models and the correctness of the stability analysis results are verified by experiments.